Phenolic content screening and in vitro antioxidant evaluation for radical scavenging activity of methanolic cladodes extract of Opuntia cochenillifera(L.) Mill - Osman, Muhammad Faris; Mat So'ad, Siti Zaiton (Malaysian Pharmaceutical Society, 2015)
Opuntia cochenilifera is a tropical cactus from the family Cactaceae. It is commonly planted as an ornamental plant in Malaysia.The objectives of this study were to screen for phenolic content, optimize chromatographic system for thin layer chromatography (TLC) analysis and evaluate the antioxidant activity of methanolic cladodes extract of Opuntia cochenillifera (L.) Mill. by using DPPH radical scavenging method. Observation of the chromatograms under visible light showed that the best compounds separation was achieved with the chromatographic system of chloroform-methanol with ratio 90:10. The presence of phenolic compounds were detected by staining the chromatogram with 10% methanolic ferric chloride reagent. At the highest concentration tested (1 mg/mL), methanolic cladodes extract of Opuntia cochenillifera showed 41.5% DPPH radical inhibition in comparison with gallic acid, which showed 95.2% DPPH radical inhibition. The results clearly indicated that the free radical scavenging activity of methanolic cladodes extract of Opuntia cochenillifera was lower than the standard gallic acid. The current study provides important baseline information to explore the potential use of Opuntia cochenillifera as an ingredient in local nutraceutical and cosmeceutical products.